In vitro models of dermatophyte infection to investigate epidermal barrier alterations. Issue 8 (28th August 2018) - Faway, Émilie; Lambert de Rouvroit, Catherine; Poumay, Yves
Abstract: Fungal infections of the skin, known as dermatophytoses, are initiated at the epidermal barrier and lead to dysfunctions of the stratum corneum and cornified skin appendages. Dermatophytosis affects a significant part of the human population and, despite the availability of effective treatments, its prevalence is still increasing. Numerous dermatophyte species are able to induce lesions in both animals and humans, with different clinical pictures and host inflammatory responses. The understanding of the infectious process and of tissue responses has been impeded by discrepancies between observations in vivo or in research models. Indeed, cells cultured as monolayers do not undergo the keratinization process required to study the adherence and invasion of dermatophytes. Animal models lack relevance to study human dermatophytosis because of species‐specific differences in the development of lesions and inflammatory responses. This review focuses on the recent development of cultured human skin equivalents, which partly overcomes those limitations and allows improved understanding of the pathogenesis of dermatophytosis in human being, especially the impacts of infection on epidermal barrier integrity.